La subjetividad como potencial democratizador: análisis de la esfera pública desde la teoría de la acción comunicativa - Rommy Morales Olivares; Andrea Silva Tapia (Ciências Sociais Unisinos)
The present article discusses, on the basis of Jürgen Habermas views, the importance of subjectivity in the constitution of a democracy where the processes of change come from popular sovereignty. For this purpose it analyzes the experience of changes made by the subjects in the modernization processes in Chile and its relation with the potential for political action. This experience represents either a restriction or a potential both for the development of action and the expression of civil society will in the public sphere. It shows that the more precarious the experience of change is, the smaller will be peoples ability to exercise their citizenship in the public political space.